Low-cost Y-type zeolite/carbon porous composite from coal gasification fine slag and its application in the phenol removal from wastewater: fabrication, characterization, equilibrium, and kinetic studies. Issue 11 (1st March 2022) - Chai, Zhen; Lv, Peng; Bai, Yonghui; Wang, Jiaofei; Song, Xudong; Su, Weiguang; Yu, Guangsuo
Abstract : A method is presented for preparing a Y-type zeolite/carbon composite with coal gasification fine slag for removing phenol in wastewater. Abstract : As an industrial solid waste, coal gasification fine slag (CGFS), which consists of many elements, such as silicon, aluminum, and carbon, could be used as an important resource. Therefore, this solid waste was used as a raw material to prepare high-value-added adsorption material for the treatment of industrial wastewater in this study. A hydrothermal synthesis method was applied to convert CGFS into a Y-type zeolite/carbon porous composite. The effects of time and temperature on the synthesis were studied. XRD, SEM, and other techniques were used to analyze the material and its physicochemical properties. Additionally, the adsorption performance of the material for phenol was studied. The results showed that the composite has better adsorption capacity for phenol than CGFS. The Freundlich model and pseudo-second-order kinetics well fitted the adsorption behavior of the composite, which demonstrated that the adsorption of phenol was dominated by chemical adsorption.